2018
DOI: 10.1021/acs.jafc.8b00491
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of 24-Methylenecyloartanyl Ferulate on A549 Nonsmall Cell Lung Cancer Cells through MYBBP1A Up-Regulation and AKT and Aurora B Kinase Inhibition

Abstract: Lung cancer is the second most prevalent cancer. Nonsmall cell lung cancer (NSCLC) is the most common type of lung cancer. The low efficacy in current chemotherapies impels us to find new alternatives to prevent or treat NSCLC. Rice bran oil is cytotoxic to A549 cells, a NSCLC cell line. Here, we identified 24-methylenecyloartanyl ferulate (24-mCAF) as the main component responsible for the cytotoxicity in A549 cells. An iTRAQ-based quantitative proteomics analysis revealed that 24-mCAF inhibits cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…Phenylpropanoid glycosides exert several biomedical effects, such as anti‐viral (Kernan et al., 1998), anti‐bacterial (Didry et al., 1999), anti‐inflammatory (Díaz et al., 2004), and anti‐obesity activities (Yang et al., 2015). Similarly, γ‐oryzanol exerts several biomedical effects, such as anti‐hyperlipidemic (Ghatak & Panchal, 2012a), anti‐diabetic (Ghatak & Panchal, 2012b), anti‐inflammatory (Rao et al., 2016), and anticancer activities (Doello et al., 2018). The concentrations of phenylpropanoid glycosides were higher in japonica cultivars than in indica cultivars, and the quantitative trait loci (QTLs) for the concentrations of phenylpropanoid glycosides were detected (Nakano et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Phenylpropanoid glycosides exert several biomedical effects, such as anti‐viral (Kernan et al., 1998), anti‐bacterial (Didry et al., 1999), anti‐inflammatory (Díaz et al., 2004), and anti‐obesity activities (Yang et al., 2015). Similarly, γ‐oryzanol exerts several biomedical effects, such as anti‐hyperlipidemic (Ghatak & Panchal, 2012a), anti‐diabetic (Ghatak & Panchal, 2012b), anti‐inflammatory (Rao et al., 2016), and anticancer activities (Doello et al., 2018). The concentrations of phenylpropanoid glycosides were higher in japonica cultivars than in indica cultivars, and the quantitative trait loci (QTLs) for the concentrations of phenylpropanoid glycosides were detected (Nakano et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis including randomised clinical trials denoted that rice bran oil intake resulted in the reduction of LDL-cholesterol and total cholesterol, hence reducing cardiovascular disease risk 7. The cholesterol lowering effect may be related to the triterpene alcohols, a part of γoryzanol, that play an important role on inhibiting cholesterol synthesis and absorption 21 . The cytotoxic properties of rice bran, particularly the oil fraction have also been explored in recent years, mainly in cancer cells 22 and mice 23 . The authors reported an inhibitory growth effect of γ-oryzanol on colon and lung cancer cell lines 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic properties of rice bran, particularly the oil fraction have also been explored in recent years, mainly in cancer cells 22 and mice 23 . The authors reported an inhibitory growth effect of γ-oryzanol on colon and lung cancer cell lines 22,23 . Most of the human studies regarding rice bran bioactivity have been focused on the whole bran or in the oil fraction and individual compounds especially ferulic acid and γ-oryzanol are considered the main contributors to human health improvement 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Barley contains a lot of functional compounds (e.g., flavanols) 34 and is used for not only staple food but also many food productions (e.g., bread and beer). More recently, although limited to the cell experiments, it has been reported that 24MCA-FA has anti-cancer effects on human breast and lung cancer cells 30,35 . Considering the increasing utilization of barley in food production, this study provides the beneficial information of 24MCA-FA and 24MCA-CA of barley, thus contributes to future application of barley as a source of 24MCA-FA and 24MCA-CA.…”
Section: Resultsmentioning
confidence: 99%